Long-term wffects of whole-body vibration in trained adolescent swimmers: Does it increase strength, power, and swimming performance? - Muniz-Pardos, B.; Gómez-Bruton, A.; Matute-Llorente, Á.; González-Agüero, A.; Gómez-Cabello, A.; Casajús, J. A.; Vicente-Rodriguez, G. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To examine the effects of a 6-month whole-body vibration (WBV) training on lower-body strength (LBS), lower-body power (LBP), and swimming performance in adolescent trained swimmers. Methods: Thirty-seven swimmers (23 males and 14 females; 14.8 [1.3] y) were randomly assigned to the WBV (n=20) or the control group (n=17). Isometric LBS (knee extension and half squat) and LBP (vertical and horizontal jumps and 30-m sprint) tests were performed before and after the intervention period. Swimming performance times in 100 m were collected from official competitions. As time×sex interaction was not found for any variable (P>.05), males and females were analyzed as a whole. Results: Within-group analyses showed a most likely beneficial moderate effect of WBV on isometric knee extension (effect size [ES]=0.63), 30-m sprint test (ES=0.62), and 100-m performance (ES=0.25), although these were corresponded with comparable small to moderate effects in the control group (ES=0.73, 0.71, and 0.20, respectively). The control group obtained a small possibly beneficial effect of swimming-only training on vertical jump performance, whereas no effect was observed in the WBV group. Unclear effects were observed for the rest of the variables assessed. Between-group analyses revealed unclear effects of WBV training when compared with the control condition in all studied variables. Conclusions: There is no current evidence to support the use of WBV training, and therefore, coaches and sports specialists should select other methods of training when the aim is to increase LBS, LBP, or swimming performance.